Metabolic syndrome in patients living with HIV/AIDS followed up at a tertiary hospital in Ceará (Research, Society and Development, 2025)
Introduction: There is a growing number of Patients Living with HIV/AIDS (PLWHA) over 50 years of age, who require good viral control and prevention and management of chronic diseases, such as Metabolic Syndrome (MS). Objective: To evaluate the risk factors for MS in PLWHA. Methods: This is an observational, cross-sectional, retrospective study with a cohort of PLWHA followed in a tertiary hospital. Results: The study involved 195 patients. Of these, 71 had MS and 124 did not. Of the patients with MS, the majority had a high Body Mass Index (BMI): 54.9%, uncontrolled blood pressure: 69%, alterations in HDL: 90% of men, 95.2% of women, Triglycerides: 62% and Glycemia: 85%. The value of Viral Load and CD4 was irrelevant, the majority were undetectable: 83.1% and with CD4>350: 87.1%. Conclusion: In general, high BMI, dyslipidemia and worse glycemic control were the most contributing factors to MS in this sample.